О формировании двух типов мартенситных фаз при пластической деформации аустенитной хромоникелевой стали - Ольшанецкий, В.Е.; Снежной, Г.В. (Физика и техника высоких давлений, 2013)
С использованием термодинамического анализа рассмотрена физическая природа формирования ε- и α′-мартенситов при деформации аустенита одноосным сжатием. Предложена схема зависимости удельных энергий аустенита и промежуточных мартенситных фаз ε и α′ от величины внешнего давления. Показано, что склонность аустенита к возникновению фазовой смеси ε- и α′-мартенситов зависит от содержания Ni. На основании чувствительного магнитометрического метода определены начальные стадии превращения аустенита в ε- и α′-мартенситы деформации. З використанням термодинамічного аналізу розглянуто фізичну природу формування ε- і α′-мартенситів при деформації аустеніту одноосьовим стисненням. Запропоновано схему залежності питомих енергій аустеніту й проміжних мартенситних фаз ε і α′ від величини зовнішнього тиску. Показано, що схильність аустеніту до виникнення фазової суміші ε- і α′-мартенситу залежить від вмісту Ni. На основі чутливого магнітометричного методу визначені початкові стадії перетворення аустеніту в ε- і α′-мартенсити деформації. Austenitic steels are used as materials that operate at high pressures. Steels of different chemical composition have different degrees of stability of the austenite to martensite transformation in the course of deformation. Using a sensitive magnetometer method accounting for magnetization of paramagnetic austenite, very low content of martensite deformation in volume percent were identified. Studies on detection of the first portions of the martensite during plastic deformation of austenite allowed classification of the state of austenite in sample steels as follows: stabilized austenite (X10CrNi23-18), moderately unstable austenite (X10CrNi16-13) and highly unstable austenite (X10CrNi18-9). The schemes of pressure dependences of the specific free energy of austenite and intermediate martensite phases (ε-and α′-martensite) were offered. It was shown experimentally that austenite can be converted both to α′- martensite, and to intermediate ε-martensite which precedes the appearance of the ε- martensite shown experimentally. The experimental data confirmed that in steels with a high stacking fault energy, deformation martensite is formed according to the scheme of γ → α′, and in alloys with low stacking fault energy, the scheme γ → ε → α′ is realized. The increase of the paramagnetic susceptibility of austenite is observed under uniaxial compression of totally austenized samples. This phenomenon is associated with changing of the electronic structure of atoms under pressure.